2016
DOI: 10.21886/2219-8075-2016-4-32-38
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF VITAMIN D RECEPTOR GEN 283 A>G (BSMI) POLYMORPHISM ON OSTEOPOROSIS IN POSTMENOPAUSAL WOMEN

Abstract: Цель: изучить ассоциации полиморфизма 283 A>G (BsmI) гена VDR с остеопоротическими изменениями в различных участках скелета у женщин в постменопаузальном возрасте. Материалы и методы: обследованы 525 женщин в постменопаузе. Остеоденситометрия выполнялась методом двухэнергетической рентгеновской абсорбциометрии. Полиморфизм 283 A>G (BsmI) гена VDR исследовался методом ПЦР в режиме реального времени. Результаты: установлены корреляционные связи (P<0,05) минеральной плотности поясничных позвонков L1-L4, проксимал… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study enrolled 65 patients females the mean age of all subjects was 64. 16 which confirmed that fractures rise exponentially with advancing age, also Albrand et al 17 in a cohort study of 672 healthy postmenopausal women established that age 65 or more is an independent risk factor for developing fractures.…”
Section: Discussionmentioning
confidence: 69%
“…The study enrolled 65 patients females the mean age of all subjects was 64. 16 which confirmed that fractures rise exponentially with advancing age, also Albrand et al 17 in a cohort study of 672 healthy postmenopausal women established that age 65 or more is an independent risk factor for developing fractures.…”
Section: Discussionmentioning
confidence: 69%